KEBIJAKAN KEPALA MADRASAH DALAM MENINGKATKAN KEPROFESIONALISME GURU DI MI SALAFIYAH SIDORENGGO AMPELGADING MALANG - Ida Lailatun Ni’mah; Ika Ratih Sulistiani; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
The principal's policy in improving teacher professionalism will certainly greatly help the council of teachers to deepen an expertise in their profession.There are several policies made by school principals in improving the professionalism of MI Salafiyah teachers, including:1) the teacher must have a S1 diploma. 2) include the teacher council in education activities and professional teacher training. 3) involving the teacher council in education and training activities, seminars, workshops, workshops within the scope of the Minimal completeness criteria, and 4) including teacher working groups. In carrying out a policy certainly does not run smoothly without obstacles. obstacles faced by the principal, including:1) family problems. 2) division of time (time of activities always collide). 3) the location of the madrasa is far from urban areas. 4) internet access is inadequate. 5) discipline, and 6) the ability to control IT is of low quality.Keywords: policy, principal, teacher professionalism